Increased long-term central memory T cells in patients with retreatment pulmonary tuberculosis - Yao, Xin; Cai, Haomin; Chen, Jianxia; Yu, Fangyong; Wu, Xiaocui; Shi, Yarong; Hu, Yang; Xu, Yuyan; Xu, Qinghua; Liu, Zhonghua (Frontiers in Immunology, 2025)
BackgroundT cells are crucial in controlling Mycobacterium tuberculosis infection and disease progression. Nevertheless, the specific functions and changes of T lymphocyte subsets in retreatment tuberculosis remain poorly understand. The study aims to identify the changes in T lymphocyte subsets and the immunoprotective effect of TCM in retreatment tuberculosis.MethodWe collected venous blood from the participants and assessed using flow cytometry. Univariate analysis and regression model were used to evaluate the changes of T lymphocyte subsets and key subsets in retreatment tuberculosis.ResultsIn the study, while the frequencies of CD4 and CD8 T cells were similar between primary and retreatment patients, retreatment patients exhibited a significant increase in TCM (P < 0.05), which may represent a protective factor for retreatment (adjusted OR=0.926, 95%CI: 0.860-0.996, P < 0.05) (adjusted OR=0.951, 95%CI: 0.912-0.992, P<0.05). Furthermore, TCM significantly increased in retreatment patients who achieved cure (P < 0.05), though were similar between the cure and no-cure for primary patients; The potentially protective effect of TCM in patients with repeated infection may possibly contribute by improving the efficacy of retreatment chemotherapy (adjusted OR=0.803, 95%CI: 0.677-0.953, P < 0.05) (adjusted OR=0.890, 95% CI: 0.812-0.976, P<0.05), particularly in those with lung injury (adjusted OR=0.780, 95% CI: 0.635-0.957, P< 0.05) (adjusted OR=0.805, 95% CI: 0.660-0.983, P<0.05).ConclusionDevelopment of adjunct immunotherapies for increasing TCM responses may improve the efficacy of retreatment tuberculosis with existing and with novel chemotherapies.